Measurements of Radiation Components at Mizuho Station, East Antarctica in 1979 - Yamanouchi, Takashi; Wada, Makoto; Mae, Shinji; Kawaguchi, Sadao; Tsukamura, Koji (1981)
P(論文) Radiation budget measurements were made at Mizuho Station under the program of POLEX-South. Global and reflected shortwave down-ward and upward longwave radiations were measured at the snow surface and at the top of a 30m tower. Direct solar radiation was also measured at the snow surface. The spectral measurements of shortwave radiation divided into four wavelength regions were made. Sensitivity constants of the pyranometers used for the measurement of global and reflected radiations showed large deviation from the cosine law response at a low solar elevation. Field calibration of the pyranometers was made extensively and some realistic equation to derive the global radiation under a broken sky from several calibration factors was proposed. As for the longwave radiation measurements, the pyrgeometer was equipped with a simple shading ring in order to eliminate the heating effect of the hemispherical dome due to solar radiation. Diurnal and seasonal variations of radiation components are shown and those of the net radiation are also given. Daily totals of the net radiation remain negative even in the summer for the clear sky, on account of high albedo of the snow surface and large upward longwave radiation compared with the downward. Downward longwave radiation was much more sensitive than the global radiation to the cloud amount and controlled the daily variations of the net balance. departmental bulletin paper